Maintaining National Adab in the Digitalization Era: A Case Study of Points of Value in the Arrays of the Jula-Juli Ludruk Song in East Java - Juairiah Juairiah; Sugit Zulianto (Pusat Unggulan Ipteks Javanologi Universitas Sebelas Maret, 2023)
AbstractThe morals of life are often spoken and passed down by the ancestors in the form of songs accompanied by Javanese gamelan. It was intended to maintain the quality of the civilization of the coming regeneration. This study aims to describe the values of sublime speech values in the chants of songs sung by comedians of the ludruk arts in East Java. Using a qualitative case study type approach, the source of the data is in the form of widely published documents of the July-July hymns. Verbal data collected were analyzed descriptively-qualitatively. The results of the research show that the lines of the jula-juli hymn contain substance in various fields of life. As an example, the points of civility in the global era are presented, namely (1) nationalism, (2) heroism, (3) education, and (4) security, (5) economy, and (6) religion. From these findings it can be concluded that etiquette for life needs to be taught through oral literary arts, especially songs in jula-juli so that the dynamics of regeneration remain grounded and side with the identity of the ancestor's speech.Keywords: nation's manners, songs, jula-juli ludruk